Actualization of Education Moral Values in the Poems of Sun Ngawiti in the Leadership of Kiai Achmad Sa'dulloh Majdi - Asdlori; Siswadi; Cubbi Syauqi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This research was intended to describe the actualization of moral values in Sun Ngawiti's poem on the leadership of the Kiai Achmad Sa'dulloh Majdi at the Al-Ittihad Banyumas Foundation. This research used qualitative research and used interview, observation and documentation techniques as collecting the data. The data were analyzed using the data analysis technique model of Miles and Huberman. The result showed that there were three moral values actualized in Sun Ngawiti's poem in the leadership of Kiai Achmad Sa'dulloh Majdi, namely discipline, patience and perseverance. The actualization of these three education moral values has made Sun Ngawiti's poem in the leadership of Kiai Achmad Sa'dulloh Majdi as a person who can prove the harmony between written, oral and deeds. Through the discipline, patience and perseverance, the Kiai Achmad Sa'dulloh Majdi has also succeeded in developing various madrasas under the auspices of the al-Ittihad foundation. Keywords:  Education Moral Value, Sun Ngawiti Poem, Leadership Kiai